SYSTEMYMATERIALNOHO IMPROVING SUPPLY LLC "MALINOVSKY GLASS FACTORY» - and (Municipal economy of cities. Series: «Economy science», 2013)
The models of inventory management are considered. The ABC-XYZ analysis of raw materials supply is conducted. The nature of demand fluctuations for raw materials is analyzed, and the optimal inventory management model for the enterprise is offered.